'It's a fix!' The mediative influence of the X Factor tribe on narrative transportation as persuasive process. Issue 2 (21st March 2013) - Richardson, Brendan; Hassan, Louise M.; Michaelidou, Nina
ABSTRACT This paper explores the mediative effect of consumer tribalism on the concept of narrative transportation as an alternative form of persuasion process. It provisionally identifies instances where persuasion seems to take place via immersion in a reality TV show narrative, rather than via critical engagement with messages. It identifies several mediative effects of consumer tribalism on such a persuasive process and points to the possibility that such mediative effects include not only initial reinforcement of the persuasiveness of the narrative but also reinforcement of an emergent cynicism when trust in the narrative begins to break down. In finding some initial evidence to suggest that this breakdown in trust may be brought about by a failure on the marketer's part to support tribal linking value, the paper also proposes the concept of spurious tribalism as a means to more fully dimensionalise the possible mediative effects of tribal activity on a narrative's capacity to engage its intended audience. Implications for further work are proposed, and limitations of the current work are identified. Copyright © 2013 John Wiley & Sons, Ltd.